Serious games as a virtual training ground for relocation to a new healthcare facility. Issue 13 (3rd October 2016) - Merschbrock, Christoph; Lassen, Ann Karina; Tollnes, Tor; Munkvold, Bjørn Erik
Abstract : Purpose: This paper aims to enquire into how building information modelling (BIM) and gaming can be integrated to support professionals in their learning about the spatial layout of a new building. This knowledge is important to prepare building operation and facilities management (FM). Design/methodology/approach: Ingrained in task–technology fit theory, this paper reports from a case study of a serious game staged in the graphical environment of a building information model. A series of interviews with the client, subject-matter experts and software developers involved in developing the game were conducted. The industrial setting for the study is a major hospital construction project in Norway. The project has been awarded BuildingSMART's 2015 award for "outstanding open BIM practice", making it Norway's role model for BIM practice. Findings: Importing and exporting geometry from BIM into a game engine remain challenging. The transfer of data between the two requires workarounds using intermediary software. Apart from issues related to technical interoperability, several sociotechnical challenges influential for the integration of BIM and gaming have been identified, related to: the collaboration among construction, operational and gaming experts; clear communication of information needs; and better contractual agreements. Research limitations/implications: BIM's geometric and semantic data enabled the creation of a sophisticated game for preparing building operation. Test-users perceived the game to be superior to classroom teaching for learning about the spatial layout of the building. However, quantifying the business value of the game for operation after occupancy of the new facilities was beyond the scope of this study. Originality/value: The work presented exemplifies a novel application area of BIM and gaming technology in FM. The findings presented in this article are relevant for professionals and scholars seeking to expand the utility of BIM for starting up the operation of new facilities.